Edukacja w oswajaniu z tematyką niepełnosprawności - Banach, Iwona (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
School is a place where educational work is undertaken to promote acceptance and tolerance towards differences of others. Teachers take action to shape appropriate attitudes towards people with disabilities and one of the most appropriate way is to introduce children and young people to the hierarchy of values.
Keywords: disability; education; social integration